2004
DOI: 10.1007/s00181-004-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Fractional cointegration and the term structure

Abstract: According to the expectations theory of the term structure of interest rates, the yield spread between long-term and short-term interest rates is an optimal predictor of future changes in short rates over the long-run. Results concerning the empirical validity of this hypothesis are not unanimous. These contradictions may be due to the fact that the traditional concept of cointegration is too restrictive. We refer here to the concept of fractional cointegration introduced by Granger (1986). We study the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…This choice is consistent with results in the applied cointegration literature, which typically produces a double negative: we cannot reject the hypothesis that inflation and nominal yields are both nonstationary and not cointegrated. Examples include Lardic and Mignon () and Hjalmarsson and Österholm (). In their critical review of the literature, Neely and Rapach (, p. 609–610) conclude that “… studies [of real rates] often report evidence of unit roots, or—at a minimum—substantial persistence.”…”
Section: Measuring Inflation Variance Ratiosmentioning
confidence: 99%
“…This choice is consistent with results in the applied cointegration literature, which typically produces a double negative: we cannot reject the hypothesis that inflation and nominal yields are both nonstationary and not cointegrated. Examples include Lardic and Mignon () and Hjalmarsson and Österholm (). In their critical review of the literature, Neely and Rapach (, p. 609–610) conclude that “… studies [of real rates] often report evidence of unit roots, or—at a minimum—substantial persistence.”…”
Section: Measuring Inflation Variance Ratiosmentioning
confidence: 99%
“…Intuitively, if interest rates are integrated of order one, the expectations hypothesis implies that the spread between any pair of yields is stationary. Following Engle and Granger's early work, several studies have taken a similar path and have found only mixed evidence for the expectations hypothesis; see, for example, Campbell and Shiller (1987), Boothe (1991), Hall et al (1992), Zhang (1993) and Lardic and Mignon (2004).…”
Section: Introductionmentioning
confidence: 96%
“…Intuitively, if interest rates are integrated of order one, the expectations hypothesis implies that the spread between any pair of yields is stationary. Following Engle and Granger's early work, several studies have taken a similar path and have found only mixed evidence for the expectations hypothesis; see, for example, Campbell and Shiller (1987), Boothe (1991), Hall et al (1992), Zhang (1993) and Lardic and Mignon (2004).…”
Section: Introductionmentioning
confidence: 96%